The Psychological Impact of COVID-19 Among Pakistani Adults in Lahore - Majeed, Saima; Schwaiger, Elizabeth Maria; Nazim, Abia; Samuel, Ivan Suneel (Frontiers in Public Health, 2021)
Background: In the wake of the world-wide spread of the novel corona virus and the resultant restrictive measures, mental health has become a crucial issue. Physical health is not the only aspect of humans that is at risk. World-wide, the rates and severity of mental illness are being significantly impacted by this pandemic. Two scales have been validated to measure the impact of COVID-19 on levels of anxiety and obsessional thinking in clinical and non-clinical populations. The present study was designed to investigate the levels of anxiety and obsessions related to COVID 19 in the general public of Lahore, Pakistan. Materials and Method: Data was collected via snowball sampling from 9th May to 19th May. An online survey consisting of a demographic profile and two scales: The coronavirus anxiety scale (CAS; Lee,2020) and Obsession with COVID-19 Scale (OCS; Lee, 2020) was sent through email, WhatsApp and Facebook groups to adults (18 years and above) of Lahore, Pakistan. Results: A total of 240 individuals (20% men and 80% women) recorded their responses. the majority belonged to a nuclear family system (60%) and their education level ranged from high school to Ph D. The cut off score for probable dysfunctional coronavirus anxiety and obsession levels was not met within this sample (CAS M = 3.24, SD = 4.21; OCS M = 4.14, SD = 3.15), suggesting that the general population of Lahore, Pakistan is not suffering from dysfunctional anxiety or obsessions related to COVID-19. Forty-seven participants’ score on OCS and thirty-five participants’ scores on CAS were above the cut off i.e ≥7 and ≥9 respectively. The results of the correlation analysis showed a significant positive relationship (.619**